Industri Pariwisata dan Ekonomi Kreatif di Dusun Pancot, Keluruhan Kalisoro, Tawangmangu - Haryatno, Yulius Rudi; Nugroho, Suryo; Edy, Irwan Christanto (Jurnal Pengabdian Bukit Pengharapan, 2023)
The aim of this community service activity is to provide knowledge and motivation for tourist village communities and local stakeholders to enter the world of the tourism industry. This is important to do so that the tourism potential in rural areas truly brings blessings to the local community, not to corporations. The way rural communities "take" advantage of today's tourism developments is through developing the creative economy. The methods in this activity are Focus Group Discussion (FGD) and counseling. This activity was enthusiastically attended by the Karangtaruna group. They are also committed to collaboration with several creative groups that already exist in Pancot Hamlet, such as the Gita Laras group and the Reog group, to continue to consistently develop the creative industry.